Using kinetics and modeling to predict denitrification fluxes in elemental‐sulfur‐based biofilms. Issue 10 (12th July 2019) - Wang, Yue; Sabba, Fabrizio; Bott, Charles; Nerenberg, Robert
Abstract: Elemental sulfur (S 0 ) can serve as an electron donor for water and wastewater denitrification, but few researchers have addressed the kinetics of S 0 –based reduction of nitrate (NO3 − ), nitrite (NO2 − ), and nitrous oxide (N2 O). In addition, S 0 ‐based denitrifying biofilms are counter‐diffusional. This is because the electron donor (S 0 ) is supplied from the biofilm attachment surface while the acceptor, for example, NO3 −, is supplied from the bulk liquid. No existing mathematical model for S 0 ‐based denitrification considers this behavior. In this study, batch tests were used to determine the kinetic parameters for the reduction of NO3 −, NO2 −, and N2 O. Additionally, a biofilm model was developed to explore the effects of counter‐diffusion on overall fluxes, that is, the mass of NO3 − or NO2 − removed per unit biofilm support area per unit time. The maximum specific substrate utilization rates ( q ˆ ) for NO3 −, NO2 −, and N2 O were 3.54, 1.98, and 6.28 g N g COD −1 ·d −1, respectively. The maximum specific growth rates ( µ ˆ ) were 0.71, 1.21, and 1.67 d −1 for NO3 − to NO2 −, NO2 − to N2 O, and N2 O to N2, respectively. Results suggest that the observed NO2 − accumulation during S 0 ‐based denitrification results from a low q ˆ for NO2 − relative to that for NO3 − . The high q ˆ for N2 O, relative to that for NO3 − and NO2 −, suggest that little N2 O accumulation occurs during denitrification. A counter‐diffusional biofilm model was used to predict trends for NO3 − fluxes, and confirmed NO2 − accumulation in S 0 ‐based denitrification biofilms. It also explains the observed detrimental effects of biofilm thickness on denitrification fluxes. This study allows a more accurate prediction of NO3 −, NO2 −, and N2 O transformations in S 0 ‐based denitrification. Abstract : At low biofilm thicknesses, the maximum denitrification fluxes (the maximum mass of nitrate removed per unit biofilm support area per unit time) are low due to biomass limitation. The maximum fluxes increase with increasing biofilm thickness. However, increasingly higher nitrate concentrations are needed to reach the maximum flux. The above behavior is typical of counter‐diffusional biofilms, where the electron donor and acceptor diffuse from opposite sides of the biofilm.